2008
DOI: 10.1111/j.1939-1676.2008.0030.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Recombinant Tissue Factor‐Activated Thromboelastography in 49 Dogs with Neoplasia

Abstract: Background: Abnormal routine coagulation assay results have been reported to be common in veterinary patients with neoplasia, but the overall hemostatic functional state, including hypercoagulability, has not been described. Hypothesis: The overall hemostatic functional state, including hypercoagulability, can be assessed in dogs with neoplasia by tissue factor (TF)‐activated thromboelastography (TEG). Animals: Thirty‐six dogs with malignant neoplasia and 13 dogs with benign neoplasia presented to the Small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
157
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(164 citation statements)
references
References 31 publications
7
157
0
Order By: Relevance
“…Indicators of inflammation, the APPs, total leukocyte and mature neutrophils were correlated with the thromboelastogram‐derived MA. These findings are in agreement with previous studies of other inflammatory and neoplastic conditions in which hypercoagulability was reported based on the presence of thromboemboli or changes in TEG variables 11, 12, 25…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indicators of inflammation, the APPs, total leukocyte and mature neutrophils were correlated with the thromboelastogram‐derived MA. These findings are in agreement with previous studies of other inflammatory and neoplastic conditions in which hypercoagulability was reported based on the presence of thromboemboli or changes in TEG variables 11, 12, 25…”
Section: Discussionsupporting
confidence: 93%
“…Systemic inflammation has been reported to result in activation of hemostasis,10 and subsequent alterations in the inflammatory and hemostatic variables in spirocercosis are expected. Definitions of hypercoagulability based on TEG variables have not yet been established for animals and numerous variables are used in different studies to define hypercoagulability, including maximal amplitude (MA) or global clot strength (G) alone or in combination with shortened reaction time (R), increased angle (α), or both 11, 12. Increased MA has been reported to be indicative of hypercoagulability in studies on animals,11, 13 and a single variable may be easier to interpret and may have greater clinical application.…”
mentioning
confidence: 99%
“…Studies also showed that fibrinogen concentration and platelet counts were correlated with G/MA and K time in dogs (11,12). Previous studies regarding the use of TEG showed hypercoagulability (evidenced by an increased MA) in dogs with parvoviral enteritis (13), neoplasia (14), or immunemediated hemolytic anemia (15), and hypocoagulapathy (evidenced by increased R and K, and decreased α-angle and MA) in dogs with DIC (12). Reference ranges for TEG parameters in healthy dogs were reported as follows: R, 1.8-8.6 min; K, 1.3-5.7 min; α-angle, 36-74 degrees; MA, 42-67 mm; and G value, 3.2-9.6 kdyn/cm 2 (10).…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies reported hypercoagulable results based on TEG measurements in dogs with parvoviral enteritis (24), endotoxemia (11), neoplasia (25), and immune-mediated hemolytic anemia (26). A hypercoagulable state in dogs with DCM may be due to increased catecholamine and cytokine responses, upregulation of the renin-angiotensin-aldosterone system, or increased P-selection expression during heart failure (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%